Documentary-derived chronologies of rainfall variability in Antigua, Lesser Antilles, 1770–1890 - Berland, A.J.; Metcalfe, S.E.; Endfield, G.H. (European Geosciences Union, 2013)
This paper presents the first extensive reconstruction of precipitation variability in the Lesser Antilles using historical documentary sources. Over 13 250 items of documentation pertaining to Antigua from the period 1769–1890 were consulted, including missionary, plantation and governmental papers as well as contemporary scholarly publications. Based on the predominant meteorological conditions observed throughout the island, each "rain-year" (December–November) was assigned one of five classifications (very wet, wet, "normal", dry and very dry). Local weather references relating to seven plantations in central-eastern Antigua were grouped according to dry (December–April) and wet seasons (May–November), each of which were also categorised in the aforementioned manner. Results comprise individual island-wide and central-eastern Antiguan chronologies of relative precipitation levels, spanning the rain-years 1769–70 to 1889–90 and 1769–70 to 1853–54 respectively. The former is compared with available instrumental data for the years 1870–1890. Significant dry phases are identified in the rain-years 1775–80, 1788–91, 1820–22, 1834–37, 1844–45, 1859–60, 1862–64, 1870–74 and 1881–82, while wet episodes were 1771–74, 1833–34, 1837–38, 1841–44, 1845–46 and 1878–81. Evidence for major wet and dry spells is presented and findings are evaluated within wider historical and palaeoclimatic contexts.